Mucoadhesive properties of liquid lipid nanocapsules enhanced by hyaluronic acid - Aguilera Garrido, Aixa; Molina-Bolívar, José Antonio; Gálvez Ruiz, María José; Galisteo González, Francisco (Elsevier, 2019)
In the field of drug delivery, nanoparticles (NPs) offer important advantages such as drug protection and solubilization, increased bioavailability, prolonged blood circulation time or sustained drug delivery. Regarding patients’ quality of life, the oral route is the most convenient, but developing oral therapies is a great challenge because of the physiological barriers to overcome. NPs can protect the active compound from the digestive process, but they need to diffuse through the mucus layer and be absorbed by the intestinal epithelium. Interaction between NPs and mucus can be promoted by the mucoadhesive properties of polysaccharide hyaluronic acid (HA). In this work, the interaction between mucin and liquid lipid nanocapsules loaded with Coumarin 153 and coated with HA of different molecular weights, has been evaluated by dynamic light scattering and by fluorimetric techniques, providing new insights in the investigation of this interaction. Hydrodynamic radius and z-potential data evidence that mucin and HA interact even at low mucin concentrations, and suggest that a layer of mucin is formed around the particles. FRET analysis, static fluorescence spectroscopy, anisotropy studies and time-resolved fluorescence further confirmed this interaction, allowed determination of binding constants and disclosed the different behaviour of low and high molecular weight HA.
Keywords: Ácido hialurónico; Nanocapsules Hyaluronic acid; Mucoadhesion FRET